Hak Paten dalam Tinjauan Hukum Waris Islam (Studi atas Konsep Royalti Hak Paten Menurut Perspektif Hukum Islam) - Yusnadi (Cyber Media Indonesia, 2022)
A patent is an exclusive right granted by the State to an inventor on the results of his invention in the field of technology, which for a certain period of time, carries out the inventory himself or gives his consent to another party to carry it out. This study aims to determine whether patent rights can be categorized as inherited assets. This research is library research where the descriptive method is used to describe the position of the patent rights, while the comparative method compares the patent rights with Islamic law, and the analysis method is to analyze whether a patent can be classified into inheritance law and how to inherit it. The results showed that a patent is a right that can be categorized as al-māl gahir al-mutaqawwim, which is immeasurable, and its value varies (uncertain). Patents have different characteristics from rights that can be inherited in general. The object of inheritance in a patent is the reward obtained from the use of a process or an invention that has been patented. If the patented invention is not used, nothing will be inherited from the patent right. The distribution of royalties obtained from a patent right can be carried out with several provisions, including waiting until a certain time limit, and then the property is divided based on the provisions of Islamic inheritance, or the property is directly distributed whenever there is the use of a patent by another party.